2018
DOI: 10.1038/s41598-018-29627-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Identification of PP2C Genes and Their Expression Profiling in Response to Drought and Cold Stresses in Medicago truncatula

Abstract: Type 2 C protein phosphatases (PP2Cs) represent the major group of protein phosphatases in plants and play important roles in various plant processes. In this study, 94 MtPP2C genes were identified from Medicago truncatula and further phylogenetically classified into 13 subfamilies, as supported by exon-intron organization and conserved motif composition. Collinearity analysis indicated that segmental duplication events played a crucial role in the expansion of MtPP2C gene families in M. truncatula. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 63 publications
7
34
0
Order By: Relevance
“…To study the phylogenetic relationship of the PP2C genes among cotton plants ( G. arboreum , G. barbadense , G. hirsutum , and G. raimondii ), a maximum likelihood (ML) tree was constructed with Arabidopsis using MEGA 7.0. The phylogenetic tree revealed that the PP2C genes can be further divided into 12 subgroups, as previously reported [26,27] (Supplementary Figures S1–S3). Moreover, 181 GhPP2C genes were clustered into 12 subgroups (A–L) with Arabidopsis .…”
Section: Resultssupporting
confidence: 73%
“…To study the phylogenetic relationship of the PP2C genes among cotton plants ( G. arboreum , G. barbadense , G. hirsutum , and G. raimondii ), a maximum likelihood (ML) tree was constructed with Arabidopsis using MEGA 7.0. The phylogenetic tree revealed that the PP2C genes can be further divided into 12 subgroups, as previously reported [26,27] (Supplementary Figures S1–S3). Moreover, 181 GhPP2C genes were clustered into 12 subgroups (A–L) with Arabidopsis .…”
Section: Resultssupporting
confidence: 73%
“…Further, the homologs of MtPP2C92 and MtPP2C65 in Arabidopsis ( ABI1 and ABI2 , respectively) are the most well-documented PP2C genes that are ABA-dependent and are active under abiotic stresses [ 163 , 165 ]. The MP2C (homolog with AP2C1 ) in alfalfa acts as a negative regulator of the MAPK pathway in cold and drought [ 167 , 168 ]. The AP2C2 (homolog MtPP2C72 ) regulates ROS levels in response to biotic and abiotic stresses [ 168 ].…”
Section: Genes Regulating Ros Homeostasis In Abiotic Stressmentioning
confidence: 99%
“…The MP2C (homolog with AP2C1 ) in alfalfa acts as a negative regulator of the MAPK pathway in cold and drought [ 167 , 168 ]. The AP2C2 (homolog MtPP2C72 ) regulates ROS levels in response to biotic and abiotic stresses [ 168 ]. AP2C1 is strongly induced in response to drought and cold, while AP2C2 is less responsive [ 164 ].…”
Section: Genes Regulating Ros Homeostasis In Abiotic Stressmentioning
confidence: 99%
“…Transcriptional profiling showed that microtuber formation in D. opposita is associated with altered transcription state of PP2C, which has both positive and negative roles in ABA signaling [42]. We therefore carried out further studies to elucidate the role of ABA in microtuber formation.…”
Section: Aba Is a Positive Regulator Of Microtuber Formationmentioning
confidence: 99%